2012
DOI: 10.15376/biores.8.1.688-700
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nondestructive Methods to Evaluate Mechanical Properties of 32-Year-Old Taiwan Incense Cedar (Calocedrus formosana) Wood

Abstract: The objective of this work was to assess the physical and mechanical properties of standing Taiwan incense cedar (Calocedrus formosana) using nondestructive techniques (NDT). In addition, the relationship between characteristics of standing trees and wood properties was established. Results indicated that the velocity values and bending properties decreased as tree height increased. In addition, velocity values of specimens were greater than those of logs and standing trees. After regressive analysis, the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…These data are better than those reported by Chiu et al (2013) (R = 0.86 between MOE dyn and MOE static , 0.69 between MOE dyn and MOR dyn ). No significant correlation was observed between MOE dyn and maximum shearing stress (R = 0.45).…”
Section: Relation Among Dynamic Moe and Mechanical Propertiescontrasting
confidence: 86%
“…These data are better than those reported by Chiu et al (2013) (R = 0.86 between MOE dyn and MOE static , 0.69 between MOE dyn and MOR dyn ). No significant correlation was observed between MOE dyn and maximum shearing stress (R = 0.45).…”
Section: Relation Among Dynamic Moe and Mechanical Propertiescontrasting
confidence: 86%
“…and Chiu et al 127 reported that dynamic MOE values obtained using both TOF and resonance were higher than static MOE calculated using bending tests, though the resonance value was closer to the static values.…”
mentioning
confidence: 81%
“…[171][172][173] 2. Acoustic resonance tool errors Studies have shown that there is a strong correlation between the MOE values calculated using the acoustic resonance technique and those obtained using mechanical bending of boards 34,44,127,159,160 (see Fig. 6).…”
Section: Fakoppmentioning
confidence: 95%
See 2 more Smart Citations